A quantitative comparison of recreational spearfishing and linefishing on the Great Barrier Reef: Implications for management of multi-sector coral reef fisheries - Frisch, A.; Baker, R.; Hobbs, Jean-Paul; Nankervis, L. (Springer Verlag, 2008)
This study compared the catch composition,catch per unit eVort, and incidental impacts of spearWshersand lineWshers engaged in a structured Wshing programwhereby Wshing eVort was standardized across time, spaceand skill level. It was found that (1) the catch compositionof both groups of Wshers overlapped considerably, (2) thenumbers of target Wsh caught by spearWshers (156) andlineWshers (168) were not signiWcantly diVerent, (3) themean size of target Wsh caught by spearWshers (1.95 § 0.1 kg,§SE) was signiWcantly larger than the mean size of targetWsh caught by lineWshers (1.27 § 0.06 kg), and (4) spear-Wshers retained 43% more biomass of target species thandid lineWshers (304 versus 213 kg, respectively). However,lineWshers used »1 kg of bait for every 3 kg of target Wshthat were captured. LineWshers also caught far more undersized,undesirable, or protected Wshes (i.e., bycatch) andcaused far more pollution (i.e., lost gear) than did spearWshers.It is concluded that the overall impacts of recreationalspearWshing and lineWshing on Wshery resources of theGreat Barrier Reef are broadly equivalent (per unit of WshingeVort), and that management regulations should be applied equitably across both Wshing sectors. A management strategyof this type will simplify enforcement of Wsheries regulationsand avoid discrimination of particular Wshers in localcommunities where both Wshing methods are socially orculturally important.